2015
DOI: 10.1186/s12889-015-2017-6
|View full text |Cite
|
Sign up to set email alerts
|

Increasing physical activity in office workers – the Inphact Treadmill study; a study protocol for a 13-month randomized controlled trial of treadmill workstations

Abstract: BackgroundSedentary behaviour is an independent risk factor for mortality and morbidity, especially for type 2 diabetes. Since office work is related to long periods that are largely sedentary, it is of major importance to find ways for office workers to engage in light intensity physical activity (LPA). The Inphact Treadmill study aims to investigate the effects of installing treadmill workstations in offices compared to conventional workstations.Methods/DesignA two-arm, 13-month, randomized controlled trial … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(22 citation statements)
references
References 39 publications
0
22
0
Order By: Relevance
“…This qualitative interview investigation was part of the Inphact Treadmill Study, performed in Umeå, Sweden, during 2014-2015 [5]. Umeå is a small university city in northern Sweden and at the time of this study had a population of 118,000 inhabitants.…”
Section: Settingmentioning
confidence: 99%
See 2 more Smart Citations
“…This qualitative interview investigation was part of the Inphact Treadmill Study, performed in Umeå, Sweden, during 2014-2015 [5]. Umeå is a small university city in northern Sweden and at the time of this study had a population of 118,000 inhabitants.…”
Section: Settingmentioning
confidence: 99%
“…Employees who were interested in participating were screened via a telephone call and a visit to a hospital, where blood samples were taken. They also completed questionnaires regarding, e.g., anxiety, depression, and stressrelated exhaustion disorder [5].…”
Section: The Inphact Treadmill Studymentioning
confidence: 99%
See 1 more Smart Citation
“…R ecent research has shown that office workers spend between 66-82% of their work hours sedentarily (Bergman, Boraxbekk, Wennberg, Sorlin, & Olsson, 2015). Low energy expenditure due to lack of activities during sedentary work is a main reason for the increase in overweight and obesity (Church et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Increasing PA and decreasing sitting time could improve functions of the body such as increase metabolism system and cognition and reduce stress and pain (Bergman et al, 2015). In contrast, few studies found that people had high PA also had a high risk for WMSDs (Auvinen et al, 2007;Heneweer, Vanhees, & Picavet, 2009).…”
Section: Introductionmentioning
confidence: 99%